Feasibility and use of the mobile food record for capturing eating occasions among children ages 3–10 years in Guam - Aflague, T.; Boushey, C.; Leon Guerrero, R.; Ahmad, Z.; Kerr, Deborah; Delp, E. (MDPI AG, 2015)
Children’s readiness to use technology supports the idea of children using mobile applications for dietary assessment. Our goal was to determine if children 3–10 years could successfully use the mobile food record (mFR) to capture a usable image pair or pairs. Children in Sample 1 were tasked to use the mFR to capture an image pair of one eating occasion while attending summer camp. For Sample 2, children were tasked to record all eating occasions for two consecutive days at two time periods that were two to four weeks apart. Trained analysts evaluated images. In Sample 1, 90% (57/63) captured one usable image pair. All children (63/63) returned the mFR undamaged. Sixty-two children reported: The mFR was easy to use (89%); willingness to use the mFR again (87%); and the fiducial marker easy to manage (94%). Children in Sample 2 used the mFR at least one day at Time 1 (59/63, 94%); Time 2 (49/63, 78%); and at both times (47/63, 75%). This latter group captured 6.21 ± 4.65 and 5.65 ± 3.26 mean (±SD) image pairs for Time 1 and Time 2, respectively Results support the potential for children to independently record dietary intakes using the mFR.